Pharmacokinetics and Druglikeness of Amoxicillin Drug using SwissADME - Prasetyawan, Fendy; Saristiana, Yuneka; Mildawati, Ratna; Rhomah, Eka Hayati; Fadel, Muhammad Nurul; Besan, Emma Jayanti (Marasofi International Media and Publishing (MIMP), 2025)
Amoxicillin, a widely utilized semi-synthetic penicillin derivative, remains a cornerstone in treating various bacterial infections. Despite its extensive clinical application, a comprehensive in silico assessment of its pharmacokinetic and